The efficacy of HI-6 DMS in a sustained infusion against percutaneous VX poisoning in the guinea-pig. (1st September 2018) - Whitmore, C.; Cook, A.R.; Mann, T.; Price, M.E.; Emery, E.; Roughley, N.; Flint, D.; Stubbs, S.; Armstrong, S.J.; Rice, H.; Tattersall, J.E.H.
Highlights: HI-6 plasma levels, AChE reactivation and survival were measured concurrently in the same guinea-pigs. Intravenous infusion of HI-6 DMS, in combination with atropine, was efficacious against percutaneous VX poisoning. At 0.07 mg/kg/min, atropine without HI-6 was ineffective against 1.53 mg/kg VX administered percutaneously. Abstract: Post-exposure nerve agent treatment usually includes administration of an oxime, which acts to restore function of the enzyme acetylcholinesterase (AChE). For immediate treatment of military personnel, this is usually administered with an autoinjector device, or devices containing the oxime such as pralidoxime, atropine and diazepam. In addition to the autoinjector, it is likely that personnel exposed to nerve agents, particularly by the percutaneous route, will require further treatment at medical facilities. As such, there is a need to understand the relationship between dose rate, plasma concentration, reactivation of AChE activity and efficacy, to provide supporting evidence for oxime infusions in nerve agent poisoning. Here, it has been demonstrated that intravenous infusion of HI-6, in combination with atropine, is efficacious against a percutaneous VX challenge in the conscious male Dunkin-Hartley guinea-pig. Inclusion of HI-6, in addition to atropine in the treatment, improved survival when compared to atropine alone. Additionally, erythrocyte AChE activity following poisoning was found to be dose dependent, with an increased dose rate of HI-6 (0.48 mg/kg/min) resulting in increased AChE activity. As far as we are aware, this is the first study to correlate the pharmacokinetic profile of HI-6 with both its pharmacodynamic action of reactivating nerve agent inhibited AChE and with its efficacy against a persistent nerve agent exposure challenge in the same conscious animal.